The book of wireless a painless guide to wi-fi and broadband wireless - Ross, John 1947- (No Starch Press, 2008)
"Broadband wireless networks bring us closer to the Internet's ultimate destiny of interconnecting everyone, everywhere. But wireless networking can be a bit geeky and nerve-wracking without a proper guide." "If you're one of the last holdouts still connected to the Internet by a wire, The Book of Wireless, 2nd Edition is the book for you. You'll learn how to set up your own home (or small office) wireless network and how to use public wireless networks, safely and securely. This plain-English guide demystifies configuring and using wireless networks - everything from shopping for parts to securing your network."--Jacket.